Evaluation Of The Compound Muscle Action Potential In Diagnosis Of The Mild Carpal Tunnel Syndrome - Veysel Alcan; Murat Zinnuroğlu; Gülçin Kaymak Karataş; Mehmet Rahmi Canal (International Journal of Applied Methods in Electronics and Computers, 2016)
Carpal tunnel syndrome (CTS) is the most common entrapment neuropathy. In most patients, the diagnosis can be proposed based on patient history and clinical symptoms, with electrophysical findings. The mild CTS may not produce any nerve conduction abnormalities and this can make standard conventional tests not enough in diagnosis the mild CTS. The aim of this study was to evaluate Compound Muscle Action Potential (CMAP) morphology as more sensitive and specific parameters without any additional testing for diagnosis the mild CTS. A total of seventy seven clinically diagnosed patients with CTS were prospectively enrolled. Data was evaluated from seventy normal hands and forty six hands with the diagnosis of the mild CTS with standard electrodiagnostic (EDX) tests and clinical findings. The specificity and sensitivity rate were calculated to evaluate the utility of CMAP negative peak (NP) morphology parameters evaluated duration (CMAP NP Half-Duration and CMAP NP Full-Duration ) and area (CMAP NP Half-Area and CMAP NP Full-Area ) by comparing the standard EDX test (Median Distal Motor Latency (DML) and peak to peak amplitude of CMAP (CMAP NP Amplitude ) recorded from the abductor policies brevis (APB) muscle. Although CMAP NP Half-Duration and CMAP NP Full-Duration had no statistically significantly difference between the mild CTS and normal group (p>0.05), DML, CMAP NP Amplitude , CMAP NP Half-Area and CMAP NP Full-Area in the mild CTS group were statistically significantly different (p